2007
DOI: 10.1007/s11064-006-9255-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on Antioxidant Enzyme Activities in the Brain of Healthy Rat

Abstract: We have studied the effect of resveratrol on lipoperoxidation and antioxidant enzyme activity level in the brain of healthy rats. When intraperitoneally administered, resveratrol significantly and dose dependently decreased brain malondialdehyde level. Resveratrol also increased in a dose-dependent way brain superoxide dismutase, catalase and peroxidase activities. Optimal effect on antioxidant enzyme and lipoperoxidation products were obtained with resveratrol concentration of 12.5 mg/kg body wt. Native polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
93
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(104 citation statements)
references
References 48 publications
6
93
1
3
Order By: Relevance
“…Further, flies reared on curcumin-supplemented diet had significantly greater vertical climbing ability (Fig. 4) especially at older ages suggesting better general health condition of the flies, perhaps due to improved neuromuscular organization (Soh et al 2013) and neuroprotective activity as in the case of resveratrol (Wang et al 2002(Wang et al , 2004Araki et al 2004;Han et al 2004;Parker et al 2005;Mokni et al 2007;Chandrashekara and Shakarad 2011). Alzheimer's disease model genotypes of Drosophila adult flies showed up to 75 % improved lifespan Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Further, flies reared on curcumin-supplemented diet had significantly greater vertical climbing ability (Fig. 4) especially at older ages suggesting better general health condition of the flies, perhaps due to improved neuromuscular organization (Soh et al 2013) and neuroprotective activity as in the case of resveratrol (Wang et al 2002(Wang et al , 2004Araki et al 2004;Han et al 2004;Parker et al 2005;Mokni et al 2007;Chandrashekara and Shakarad 2011). Alzheimer's disease model genotypes of Drosophila adult flies showed up to 75 % improved lifespan Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have indicated that resveratrol can minimise the deleterious effect on cognition of aging and physical and chemical damage to the brain [1-7, 9, 10]. Furthermore, resveratrol has been shown to prevent oxidative damage [8] and to clear the beta-amyloid peptides that are associated with Alzheimer's disease [29,30]. However, there is no evidence that resveratrol enhances cognition in the absence of pathology (as is the situation in young, healthy individuals).…”
Section: Discussionmentioning
confidence: 99%
“…In rats and mice, resveratrol has been found to minimise the adverse brain and cognitive changes induced by neurologically damaging events such as streptozotocin-induced diabetes [1]; percussive cerebral trauma [2]; focal cerebral ischemia (stroke) [3]; oxidative stress caused by intracerebroventricular injection of streptozotocin [4] or cochinine [5]; and neurotoxic substances used to mimic Huntington's disease [6] and Parkinson's disease [7]. Resveratrol has been shown to decrease lipid peroxidation and up-regulate antioxidant enzymes in the brains of healthy male rats [8]. This indicates that resveratrol may protect against oxidative damage in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol was reported effective against neuronal cell dysfunction and cell death in diseases such as Huntington's disease [17] and Alzheimer's disease [18]. Treatment with single dose of resveratrol after trauma significantly ameliorated the trauma induced hippocampal neuronal loss in rats [19].Mokni et al report that resveratrol is able to cross the blood brain barrier and exerts potent antioxidant properties [20].Sahu et al study reported that gestational treatment of resveratrol prevented the prenatal stress induced memory impairment and the anxiogenic behavior, indicating its neuroprotective activity [21]. Resveratrol during pregnancy reversed the prenatal stress-induced memory impairment and oxidative damage in the offspring [22].…”
Section: Introductionmentioning
confidence: 99%